Drop-out from chronic pain treatment programmes: Is randomization justified in biopsychosocial approaches? - Aminata Bicego; Justine Monseur; Floriane Rousseaux; Marie-Elisabeth Faymonville; Nicole Malaise; Irène Salamun; Alain Collinet; Anne-Sophie Nyssen; Audrey Vanhaudenhuyse (Medical Journals Sweden, 2021)
Objective: To identify profiles of patients who are at risk of dropping out from biopsychosocial approaches to chronic pain management. Patients: A total of 575 patients were included in the study. Of these, 203 were randomized into 4 treat-ment groups: self-hypnosis/self-care; music/self-care; self-care; and psychoeducation/cognitive behavioural therapy. The remaining 372 patients were not randomized, as they presented with the demand to learn self-hypnosis/self-care, and therefore were termed a "self-hypnosis/self-care demanders" group. Methods: Socio-demographics and behavioural data were included in the analyses. Univariates analyses, comparing early drop-outs (never attended treatment), late drop-outs (6/9 sessions' treatment) and continuers were conducted in order to select variables to include in a multivariate logistic regression. Results: Univariate analyses yielded 8 variables, out of 18 potential predictors for drop-out, which were eligible for inclusion in the multivariate logistic regression. The model showed that having an intermediate or high educational level protects against dropping out early or late in the pain management process. Having to wait for more than 4 months before starting the treatment increases the risk of never starting it. Being randomized increases the risk of never starting the treatment. Conclusion: In a context in which randomization is considered a "gold standard" in evidence-based practice, these results indicate that this very principle could be deleterious to pain management in patients with chronic pain.